2012
DOI: 10.3992/jgb.7.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Using Life Cycle Assessment Methods to Guide Architectural Decision-Making for Sustainable Prefabricated Modular Buildings

Abstract: Within this work, life cycle assessment modeling is used to determine top design priorities and quantitatively inform sustainable design decision-making for a prefabricated modular building. A case-study life-cycle assessment was performed for a 5,000 ft2prefabricated commercial building constructed in San Francisco, California, and scenario analysis was run examining the life cycle environmental impacts of various energy and material design substitutions, and a structural design change. Results show that even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…'End of life' of the main function, which stands for the convertibility of the system: reuse of the container module: the basic structure can be reused without heavy interventions; component multi-functionality: the structure of the container performs both structural and closing functions, while providing a considerable mass for thermal inertia; expandability: the structural module does not correspond to the living cell, meaning that it can be used for infinite compositions; possible new reconfiguration of the system: the easy disassembly and reassembly of the joints ensures an easy and quick reconfiguration of the structural modules; module transformability: the structural module can be used in different configurations, some of which require minimal interventions; module durability: the structural module is in corten steel, which is guaranteed to resist extreme conditions, including saltiness; energy recovered at the end of the function: all the employed corten steel, which has high levels of embodied energy, can be used without additional energy for other functions (the structural module can become something else without other processes); 4. End of building life (Faludi et al 2012): reversibility of the foundation system: once unscrewed the screw foundations, the ground returns to its original state without any damage; disassembly of the components: all connections are made with clamping and thus easily separable systems; reuse of the container: the basic structure can be reused without heavy interventions; reuse of the casing components: both the finishes and the thermal insulation are mechanically fixed, so that they can be easily dismantled and reused; recycling of container components: as a last opportunity, the container is made of corten steel which can be used as a second raw material; 5. 'End of life' of the main function.…”
Section: Results: the Projectmentioning
confidence: 99%
“…'End of life' of the main function, which stands for the convertibility of the system: reuse of the container module: the basic structure can be reused without heavy interventions; component multi-functionality: the structure of the container performs both structural and closing functions, while providing a considerable mass for thermal inertia; expandability: the structural module does not correspond to the living cell, meaning that it can be used for infinite compositions; possible new reconfiguration of the system: the easy disassembly and reassembly of the joints ensures an easy and quick reconfiguration of the structural modules; module transformability: the structural module can be used in different configurations, some of which require minimal interventions; module durability: the structural module is in corten steel, which is guaranteed to resist extreme conditions, including saltiness; energy recovered at the end of the function: all the employed corten steel, which has high levels of embodied energy, can be used without additional energy for other functions (the structural module can become something else without other processes); 4. End of building life (Faludi et al 2012): reversibility of the foundation system: once unscrewed the screw foundations, the ground returns to its original state without any damage; disassembly of the components: all connections are made with clamping and thus easily separable systems; reuse of the container: the basic structure can be reused without heavy interventions; reuse of the casing components: both the finishes and the thermal insulation are mechanically fixed, so that they can be easily dismantled and reused; recycling of container components: as a last opportunity, the container is made of corten steel which can be used as a second raw material; 5. 'End of life' of the main function.…”
Section: Results: the Projectmentioning
confidence: 99%
“…Panjehpour et al thought that although prefabricated construction has many advantages, the designer should consider the problems of prefabricated systems, like the roof and walls, and integrate them into different application systems [13]. Faludi et al used the whole life cycle assessment model to evaluate the sustainability and optimal performance of prefabricated construction [14]. Through their investigation, Jaillon and Poon found that although the prefabricated building can save time and cost, few people consider the design idea of the whole life cycle, including the removal of flexible materials and efficient use of resources [15].…”
Section: International Research Statusmentioning
confidence: 99%
“…The importance of life cycle assessment (LCA) to guide the design of modular buildings has been well noted, particularly attributed to the dominance of nonoperational phases when a building's operational phase approaches net‐zero energy consumption (Faludi et al. ; Stephan et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Prefabricated modular housing has consequently arisen as a state-of-the-art means of reducing both material inputs and energy consumption during the nonoperational phases of a building's life cycle, largely attributed to economies of scale achieved during the fabrication of building modules in a factory setting (Monahan and Powell 2011;Quale et al 2012). The importance of life cycle assessment (LCA) to guide the design of modular buildings has been well noted, particularly attributed to the dominance of nonoperational phases when a building's operational phase approaches net-zero energy consumption (Faludi et al 2012;Stephan et al 2013). Although it is well established that the operational phase of a building is the most influential on its life cycle environmental impacts, a more-nuanced investigation of key impact drivers and the most influential parameters can further aid sustainable building design (Heeren et al 2015).…”
Section: Introductionmentioning
confidence: 99%